Pengaturan Jarak Tanam Optimal Untuk Meningkatkan Produktivitas Tanaman Hortikultura - Laoli, Desta Ewini; Najma (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the optimal planting distance for increasing horticultural crop productivity. Through a comprehensive literature review, the research highlights the role of plant spacing in improving photosynthesis, nutrient uptake, and crop yield. Findings indicate that efficient spacing significantly enhances resource use efficiency, reduces competition among plants, and mitigates risks such as pest outbreaks and nutrient deficiencies. The study also emphasizes the use of precision agriculture technologies, such as GIS and IoT-based tools, to customize planting distances for various crops and environmental conditions. These insights are expected to contribute to sustainable agricultural practices that optimize land use while maintaining environmental balance.